2020
DOI: 10.1002/fsn3.1536
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity analysis of the precooling process of strawberry: Effect of package designing parameters and the moisture loss

Abstract: Strawberry is one of the most perishable fruits, and precooling of strawberry increases the percentage of marketable fruits. To assess the sensitivity of strawberry cooling uniformity with respect to package vents and tray design, the previously proposed modified parallel airflow system (MPAS) was modified and a sensitivity analysis was conducted in this paper. Some improvements in homogeneous strawberry precooling process were made to give improved parallel airflow system (IPAS). To evaluate its performance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…A moisture loss of waxed citrus fruits was 0.42% during the cooling period of 17.6 hr that corresponded to an evaporative cooling of 12.79% (Lambrecht, 2012). Thus, the moisture loss term inside fruits should be included in heat sources term during the cooling process, which is consistent with the investigated results of Nalbandi and Seiiedlou (2020). This is due to the fact that the associated error can be compensated by using the mathematical coupling of the term of moisture loss to the airflow.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…A moisture loss of waxed citrus fruits was 0.42% during the cooling period of 17.6 hr that corresponded to an evaporative cooling of 12.79% (Lambrecht, 2012). Thus, the moisture loss term inside fruits should be included in heat sources term during the cooling process, which is consistent with the investigated results of Nalbandi and Seiiedlou (2020). This is due to the fact that the associated error can be compensated by using the mathematical coupling of the term of moisture loss to the airflow.…”
Section: Resultssupporting
confidence: 88%
“…Han et al (2017) found that the maximum temperature difference of a single apple was up to 0.033°C during cooling by comparing the temperature simulated with or without considering respiratory heat. Regarding strawberries, Nalbandi and Seiiedlou (2020) reported that transpiration heat could not be neglected during the cooling process, as the 7/8ths cooling time (SECT) decreased by 31% when this heat was added into the numerical model. Unfortunately, these previous researches did not analyze the sensitivities of these heat sources on various aspects of fruits cooling performances at different precooling strategies, resulting in an unclear relationship between these sensitivities and air-inflow velocities, coupled with the uncertainty of its corresponding influence magnitude.…”
mentioning
confidence: 99%
“…Thus, moisture loss plays an important role in anthocyanin degradation [46]. Therefore, several studies have investigated precooling, modified atmosphere packaging, and edible coating technologies to prevent moisture loss of strawberries, thus extending their shelf life [47][48][49]. Strawberries with an edible coating (2-3% soy protein-based or 2-3% alginate-based coating) show moisture loss of 4.41% on the 7th day of storage at 4 • C [49].…”
Section: Effect Of Combined Treatment Of Aerosolization and Uvc Led On Visual Appearance Evolution And Colour Measurement Of Soft Fresh Pmentioning
confidence: 99%
“…Usually, there are several limiting factors, including fruit variability, measuring decay and amount control of fungal spores, or the availability of proper climatic chambers to reproduce specific cold chains realistically. Previous studies have discussed the optimal design of (ventilated) packaging in order to make cooling processes (e.g., precooling) more efficient (Ferrua & Singh, 2011;Nalbandi & Seiiedlou, 2020). Furthermore, it was investigated how humidity-related effects impact the shelf life of packed strawberries.…”
Section: Introductionmentioning
confidence: 99%